Political roots of religious exclusion in Turkey - Nefes, T (Oxford University Press, 2017)
Do perceived political threats lead to religious exclusion? This study explores the political rationale of the exclusionary attitude towards non-Muslim minorities in Turkey. It relies on a qualitative content analysis of the discussions on the Armenian, Greek and Jewish foundations in the Turkish parliament in the 2000s. While doing so, the research brings together the academic literatures on the perception of religious minorities in Turkey with the group threat perspective. The findings show that the exclusionary statements about the non-Muslim minorities are often justified by suspecting them as potential plotters of the dismemberment of the country. The paper concludes that to achieve an inclusive political culture in Turkey, it is imperative to understand the perceived national security threats. It also underlines that parliamentary debates constitute an ideal resource for research, which deserves greater attention.